The Colors of Central and Satellite Galaxies in zCOSMOS out to z ~ 0.8 and Implications for Quenching - Knobel, C; Lilly, S; Kovac, K; Peng, Y; Bschorr, T; Carollo, C; Contini, T; Kneib, J; Fevre, O; Mainieri, V; Renzini, A; Scodeggio, M; et al. (Institute of Physics Publishing, 2012)
We examine the red fraction of central and satellite galaxies in the large zCOSMOS group catalog out to z ~ 0.8 correcting for both the incompleteness in stellar mass and for the less than perfect purities of the central and satellite samples. We show that, at all masses and at all redshifts, the fraction of satellite galaxies that have been quenched, i.e., are red, is systematically higher than that of centrals, as seen locally in the Sloan Digital Sky Survey (SDSS). The satellite quenching efficiency, which is the probability that a satellite is quenched because it is a satellite rather than a central, is, as locally, independent of stellar mass. Furthermore, the average value is about 0.5, which is also very similar to that seen in the SDSS. We also construct the mass functions of blue and red centrals and satellites and show that these broadly follow the predictions of the Peng et al. analysis of the SDSS groups. Together, these results indicate that the effect of the group environment in quenching satellite galaxies was very similar when the universe was about a half its present age, as it is today.